Travel Time to Cities in Tanzania - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Reliable market accessibility data is critical to developing agricultural policies and investment plans for ensuring smallholder farmers’ market participation and their profitable farming, yet this data is less frequently updated. Most of the publicly available data are outdated and hard to reflect the rapid development of transportation infrastructure in African countries. For this, using a newly available accessibility model input dataset, such as new land cover data from satellites, crowdsourced road network data, and the updated population of major human settlements in Tanzania are used to update the existing market accessibility data and provides new market accessibility data layers benchmarking around the year 2015. The dataset includes three data layers representing travel time to the nearest market of five sizes (population of 20K, 50K, 100K), respectively, on 1 arc-minute (~1km) grids in Tanzania.